Apolipoprotein E Isoforms Differentially Regulate Alzheimer's Disease and Amyloid-β-Induced Inflammatory Response in vivo and in vitro. - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (J Alzheimers Dis, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer's disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.

Genetic Variations in ABCA7 Can Increase Secreted Levels of Amyloid-β40 and Amyloid-β42 Peptides and ABCA7 Transcription in Cell Culture Models. - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPPSwe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ40 and Aβ42 and β-secretase activity in CHO- and HEK-AβPPSwe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.